2020
DOI: 10.1007/s11207-020-1591-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Solar Eruptions with Remote and In-Situ Observations, and Modeling: The Major Solar Events on 4 November 2015

Abstract: Solar energetic particles (SEPs) are an important product of solar activity. They are connected to solar active regions and flares, coronal mass ejections (CMEs), EUV waves, shocks, Type II and III radio emissions, and Xray bursts. These phenomena are major probes of the partition of energy in solar eruptions, as well as for the organization, dynamics, and relaxation of coronal and interplanetary magnetic fields. Many of these phenomena cause terrestrial space weather, posing multiple hazards for humans and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 151 publications
0
7
0
Order By: Relevance
“…However, from inspecting Figure 13 where the HXR emission is overplotted on the dynamic spectrum, there is quite a clear relation between the radio bursts and the HXR peaks when the entire frequency band is taken into account. Cairns et al (2020) point out that a type II radio burst occurs at the time of this flare and suggest that the associated shock may be responsible for accelerating the electrons that result in the low frequency radio emission. However, considering the arguments above (points 1-4), we conclude that it is more likely that the type III radio bursts are due to pulses of electron beams accelerating along the open magnetic lines close to the QPP source region.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, from inspecting Figure 13 where the HXR emission is overplotted on the dynamic spectrum, there is quite a clear relation between the radio bursts and the HXR peaks when the entire frequency band is taken into account. Cairns et al (2020) point out that a type II radio burst occurs at the time of this flare and suggest that the associated shock may be responsible for accelerating the electrons that result in the low frequency radio emission. However, considering the arguments above (points 1-4), we conclude that it is more likely that the type III radio bursts are due to pulses of electron beams accelerating along the open magnetic lines close to the QPP source region.…”
Section: Discussionmentioning
confidence: 87%
“…However, considering the arguments above (points 1-4), we conclude that it is more likely that the type III radio bursts are due to pulses of electron beams accelerating along the open magnetic lines close to the QPP source region. Additionally, the dynamic spectra of the radio emission from kHz to GHz shows traces of type III bursts that extend to high frequencies, above the frequency of the type II burst (see Cairns et al (2020) Figure 15). This suggests that they originate from a region closer to the flare site.…”
Section: Discussionmentioning
confidence: 99%
“…Decametric to hectometric type II bursts are generally attributed to shocks driven by CMEs in the corona and heliosphere. However, several examples of type II bursts exist with starting frequencies in the decimetric range (Vrsnak et al, 1995;Cho et al, 2013;Cairns et al, 2020), and the origin of such "high-frequency" type II bursts is somewhat debated. They may be from blast waves due to impulsive heating by flares low in the corona (Magdalenić et al, 2012), driven by the shock of eruptive bubbles, or potentially due to strong lateral expansion (associated with EUV waves) during early-phase flux rope eruption (Patsourakos and Vourlidas, 2012;Nitta et al, 2014).…”
Section: Eruption-driven Shocksmentioning
confidence: 99%
“…A similar assertion can be made for the absence of type III radio bursts in some events. For example, Cairns et al (2020) recently showed an interesting study of three events on the same day, only one of which showed significant type III activity. Those events with no type III bursts were from the same active region, and perhaps provided no means of electron beam escape into the heliosphere, which points to the special configuration of the ambient coronal environment in producing such radio bursts.…”
Section: Radio-quiet Coronal Mass Ejections and Stealth Coronal Mass Ejectionsmentioning
confidence: 99%
“…Figure8displays the dynamic spectrum of a type II burst in the top panel. The event was presented in Section 5.2 ofCairns et al (2020). The emission starts at unusually high frequencies.…”
mentioning
confidence: 99%